Differences in Affective Domain Development Music Learning between Indonesia, The Netherlands, and France - Astuti, Kun Setyaning; Belly, Marlene; Maulana, Ridwan; Armini, Alice (Harmonia: Journal of Arts Research and Education, 2024)
The ‘affective domain’ supports students’ moral development, shaping their character. The research aims to investigate the music learning process in Indonesia, the Netherlands, and France and determine its contribution to the affective domain. The study adopted a mixed methods approach with sequential designs. In the first phase, qualitative data were collected through observations of learning processes as well as through interviews and document analysis. These qualitative data informed the development and administration of instruments for the second phase that measured aspects of the music learning process expected to contribute to the affective domain. Based on the analysis of 74 music learning processes, this research showed differences between the three countries in song choices and methods for developing the affective domain through music learning. Song choices in the Netherlands and France were based on the song’s potential to touch students’ feelings, while those used in Indonesia were selected to build moral character and foster national pride. In the Indonesian music learning context, persuasion and intervening were predominant methods – as they were (although to a lesser extent) in France. In contrast, the Netherlands made greater use of inculcation and, along with France, habituation.